Government Political Rhetoric and Communication in the Practice of Government Implementation - Arrianie, Lely (Dinasti Research, 2023)
The latest survey on the level of public satisfaction with the performance of President Joko Widodo LSI April 2023 shows a figure of 82 percent, the Indonesian political indicators survey also recorded a figure of 79.2 SMRC shows a figure of 81.7 percent. This high public satisfaction is the question, how is the rhetoric and political communication carried out by the government in the practice of administering government, Aristotle's Rhetorical theory developed by Richard West and Lynn H Turner and the qualitative phenomenological approach used found that; The government's political rhetoric and communication combines the concepts of ethos, logos and pathos with leadership values developed by Ki Hajar Dewantara, namely Ing Ngarso Sung Tulodo, Ing Madyo Mangun Karso and Tut Wuri Handayani. The